2011
DOI: 10.1177/0899764011411095
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and Demographic Factors for Performing Arts Attendance Across Place and Form

Abstract: Previous research seeking to explain why people attend live performing arts events has focused primarily on demographic explanations, such as the age or income of patrons. Recent research reinvigorates an old debate regarding the veracity of psychological motivations for attendance, such as an appreciation for beauty or the opportunity to socialize with others. We add to this line of inquiry by investigating how demographic and motivation explanations fare across three cities, and for three different art forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…This explanation is certainly plausible in light of the qualitative findings that indicated that perceived cultural and language barriers were particularly high amongst South Korean immigrant group. Although childhood exposure to the arts was not significant in explaining omnivorous cultural consumption, this same variable, and in line with Hager and Winkler's () work, did have a strong impact on highbrow arts consumption ( F = 4.823, sig. = 0.031; F = 6.517, sig.…”
Section: Quantitative Analysis and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This explanation is certainly plausible in light of the qualitative findings that indicated that perceived cultural and language barriers were particularly high amongst South Korean immigrant group. Although childhood exposure to the arts was not significant in explaining omnivorous cultural consumption, this same variable, and in line with Hager and Winkler's () work, did have a strong impact on highbrow arts consumption ( F = 4.823, sig. = 0.031; F = 6.517, sig.…”
Section: Quantitative Analysis and Discussionsupporting
confidence: 74%
“…Social/economic status (H2a) and childhood exposure to the arts (H2c) could not explain the cultural consumption practices of the sample, even though in the western world, these are suggested as some of the best predictors of adult participation in the arts (see Silva, ; Bennett et al ., ; Hager & Winkler, ). To understand why these variables were not significant, a number of analyses of variation were carried out to see how sample members' cultural consumption responses differed according to these items.…”
Section: Quantitative Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the work of a particular director), and reduction of negative experiences (e.g. escaping from events) (Bouder‐Pailler, ; Cuadrado and Mollà, ; Caldwell, ; Swanson et al ., ; Hager and Winkler, ; Walmsley, ). Audience behaviour, as a research topic, has garnered scholarly attention in the last three decades, mainly from the disciplines of marketing and consumer behaviour, following the ideas of broadening of marketing (Kotler and Levy, ) and consummation potential of everything individuals do (Holbrook, ).…”
Section: Introductionmentioning
confidence: 99%
“…with the world of art, actors and directors (Hager & Winkler, 2012;Montgomery, 2017;Sedgman, 2017;Wing, Glos, & Kenson, 2017).…”
mentioning
confidence: 99%